PEMANFAATAN KEMBALI LIMBAH POTONGAN KAYU MENJADI MATERIAL FURNITURE MELALUI PENDEKATAN SOCIAL ENTREPRENEURSHIP - Senain Senain; Farida Hanum (INTEGRITAS : Jurnal Pengabdian, 2018)
One of the excellent products from Situbondo regency is wooden handicraft product so easy furniture business we meet. Waste wood pieces are the remnants of wood pieces in the form of boards or small pieces that can still be seen form. Wooden board consisting of pieces of wood can be utilized into various objects used in the interior of a room. In addition to adding functionality from waste wood pieces, wooden waste board can also add aesthetic value on an object. This is because the board has different characteristics compared to ordinary wooden boards. Activities that have been done include interior design training, interior making from waste wood pieces, Business Management Training and Employee Motivation Program on UKM Meubel Heni and UKM Meubel Kyky. For 6 months the partners' activities are provided with continuous facilitation and training to produce a table of waste wood products and grow entrepreneurial spirit in all partners.